Persistence and Accumulation of Visual Memories for Objects in Scenes in 12-Month-Old Infants - Guillory, Sylvia B.; Kaldy, Zsuzsa (Frontiers in Psychology, 2019)
Visual memory for objects has been studied extensively in infants over the past twenty years, however, little is known about how they are formed when objects are embedded in naturalistic scenes. In adults, memory for objects in scenes show information accumulation over time as well as persistence despite interruptions (Melcher, 2001, 2006). In the present study, eye-tracking was used to investigate these two processes in 12-month-old infants (N = 19) measuring: (1) whether longer encoding time can improve memory performance (accumulation), and (2) whether multiple shorter exposures to a scene are equivalent to a single exposure of the same total duration (persistence). A control group of adults was also tested in a closely matched paradigm (N = 23). We found that increasing exposure time led to gains in memory performance in both groups. Infants were found to be successful in remembering objects with continuous exposures to a scene, but unlike adults, were not able to perform better than chance when interrupted. However, infants’ scan patterns showed evidence of memory as they continued the exploration of the scene in a strategic way following the interruption. Our findings provide insight into how infants are able to build representations of their visual environment by accumulating information about objects embedded in scenes.